2019
DOI: 10.1177/0887403419840804
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equality and Sentencing Outcomes: An Examination of State Courts

Abstract: The current study examined whether measures of structural gender equality conditioned the effects of defendant gender on incarceration decisions. Using data from the State Court Processing Statistics (SCPS) database, multilevel logistic regression was used to examine the relationship between both case- and county-level variables on incarceration decisions on a sample of defendants sentenced in state courts. Results indicated that women were less likely to be sentenced to prison than men, but there was no gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
0
12
0
2
Order By: Relevance
“…Research has shown that gender equality is an outcome of weakening patriarchal norms and institutional practices (Dilli et al, 2015). Furthermore, studies have shown that extralegal characteristics of a community in which a court operates, such as gender equality, influences punishment outcomes (Kim et al, 2019; Nowacki, 2020; Nowacki & Windsong, 2019). As such, gender equality may be indicative of ideological shifts in the broader communities that a court is situated in (Nowacki, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that gender equality is an outcome of weakening patriarchal norms and institutional practices (Dilli et al, 2015). Furthermore, studies have shown that extralegal characteristics of a community in which a court operates, such as gender equality, influences punishment outcomes (Kim et al, 2019; Nowacki, 2020; Nowacki & Windsong, 2019). As such, gender equality may be indicative of ideological shifts in the broader communities that a court is situated in (Nowacki, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, studies have shown that extralegal characteristics of a community in which a court operates, such as gender equality, influences punishment outcomes (Kim et al, 2019; Nowacki, 2020; Nowacki & Windsong, 2019). As such, gender equality may be indicative of ideological shifts in the broader communities that a court is situated in (Nowacki, 2020). With gender so inextricably related to punishment attitudes and support for the death penalty, the reaction to gender equality within a community remains an important factor to understand courtroom decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finalmente, algunos investigadores afirman que las decisiones judiciales pueden verse influidas, a su vez, tanto por las características de la organización en la que trabajan los jueces, esto es, el tipo de juzgado, su tamaño, su localización y la cultura judicial (Nowacki, 2019;Pina-Sánchez & Grech, 2018), como por la valoración que los propios jueces hacen de las consecuencias que pueden tener sus decisiones sobre las personas implicadas (Steffensmeier et al, 1998).…”
Section: Estudios De Sentencing En El áMbito Internacional: ¿Qué Sabemos?unclassified
“…Entre los estudios que sí hallan diferencias, son pocos los que sostienen que las mujeres reciben un trato más duro por parte de los jueces (Franklin & Fearn, 2008). La mayoría señala que las mujeres reciben un trato más benévolo que los hombres (Bontrager et al, 2013;Daly & Bordt, 1995;Herzog & Oreg, 2008;Koons-White et al, 2014;Nowacki, 2019;Pina-Sánchez & Harris, 2020;Starr, 2015;Steffensmeier, 1980, Stancu & Varona, 2017, es decir, se las condena menos que a ellos, se les imponen menos penas de prisión y estas suelen ser de menor duración (Steffensmeier & Faulkner, 1978). De hecho, los dos meta-análisis realizados hasta la fecha en esta materia (Bontrager, et al, 2013;Daly & Bordt, 1995) confirman esta idea.…”
Section: Influencia Del Género En La Toma De Decisiones Judicialesunclassified